Efficiency-First Bioacoustic Audio Event Detection Under Resource-Constrained Systems - Magalhães, André M. S.; de Oliveira, Willian D.; Garbossa, Cesar A. P.; Ventura, Ricardo V.; Sousa, Elaine P. M. de (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Passive acoustic monitoring enables wildlife biodiversity assessment and precision livestock management, yet accurate detectors remain difficult to deploy on resource-limited systems. We present a controlled evaluation of AST, SSAMBA, and MAMBASPEC on two IoT-relevant bioacoustic datasets (aSwine, AnuraSet). MAMBASPEC matches AST within 0.7 pp ROC-AUC w on AnuraSet with 80× fewer parameters and 1,617× fewer FLOPs, while SSAMBA achieves statistically indistinguishable ROC-AUC w at a 12.8× smaller footprint. Friedman tests (p<10 −3 ) and Pareto analysis indicate that MAMBASPEC is the efficiency-first choice under resource constraints, whereas SSAMBA is the accuracy-oriented choice when modest extra latency is acceptable.